(untitled) (Indian Journal of Animal Production and Management, 2014)
Development of database management software is an effective method to enter and retrieve information on each trait/animal, which subsequently adds to maintain animal health; to improve reproduction, genetics and milk production; and to optimize feeding in dairy cattle1, 2, 5. In India, efforts have been made to design herd management software at the CIRB, Hissar and at TANUVAS, Chennai. Chitale Dairy Farm, Pune is successfully using DeLaval ALPRO system for the recording of various information on buffaloes and reported 15% increase in total milk production. Many commercial livestock management software packages are also available in developed countries4. In New Zealand, the purpose of the dairy core database is to record the performance of New Zealand dairy herd and to evaluate the genetic worth of cows and bulls6. The requirement of database, however differs from herd to herd, hence, a database package was developed at IVRI in MS Access (one of the modules of MS Office)3, considering all the traits like growth, production, reproduction and health.